Relationship between higher order thinking and metacognitive skills with hands-on teaching among primary school science teachers in Jempol district - Subramaniam, Punnithann; Sulaiman, Tajularipin; Kamarudin, Nurzatulshima (Academy of Sciences Malaysia, 2020)
Higher order thinking skills and metacognitive skills are essential in generating intellectual competitiveness to meet the challenges of acquiring today’s knowledge. This study examines the relationship between higher order thinking skills (HOTS) and metacognitive skills with hands-on teaching in Science among primary school Science teachers in the Jempol district. The purpose of this study is to look at the relationship between the level of higher order thinking skills (HOTS) and metacognitive skills with hands-on teaching in Science among primary school Science teachers in the Jempol district. This study is designed using descriptive and correlation methods. This study uses the quantitative approach by using questionnaire. The findings of the quantitative analysis show that the level of thinking skills is high (M = 4.36, S.D. = 0.577) among Science teachers in the Jempol district. In addition, the findings show that the metacognitive level was high (M = 4.39, S.D. = 0.579) among Science teachers in the Jempol district. Next, the level of hands-on teaching in Science is high (M = 4.37, S.D. = 0.543) among Science teachers in this district. The findings show that there is a significant relationship between higher order thinking skills (HOTS) and hands-on teaching in Science (r = 0.739, n = 94, p < 0.01). This study shows that the relationship between metacognitive and hands-on teaching is stronger. Multiple regression analysis was conducted, and the findings show that the Beta value for metacognitive skills is higher (0.626) compared to the Beta value of higher order thinking skills (HOTS) (0.265). This study will impact science teachers in the Jempol area to focus more on higher order thinking skills (HOTS) and metacognitive teaching.